Growth Gains from Trade and Education - Kim, Yong-jin (IMF Working Papers; Working Paper, 1999)
This paper presents a multisector growth model where education enhances general human capital, which is essential for increasing or maintaining the mobility of workers across industries. The paper shows that education, combined with international trade, can affect growth positively in the long run by raising workers' ability to adapt and move easily to industries with the greatest productivity in each period. Depending on the initial ratio of general-to-specific human capital stock, multiple equilibrium growth paths can exist, including a poverty trap. If the ratio is not substantially low, trade liberalization can allow an economy in a poverty trap to transform into one with continuous education and higher output growth.